Effect of laser pointer on students\\\' levels of technical errors during intraoral radiographs - Farshid Shams; Fahime Sadat Sanaei; Nasim Azizi; Ali Peymani; Zeinab Davoudmanesh (Tehran University of Medical Sciences, 2015)
Background and Aims: According to concerns of technical errors in intraoral radiographs and reports of positive effects of central ray laser pointer on the students, technical errors and shortcomings of earlier research, this study was conducted at Department of Oral and Maxillofacial Radiology of Tehran Azad University to determine the role and use of laser pointer in the technical error made by students. Materials and Methods: This clinical trials study was carried out at the Department of Radiology, Dental School of Azad Tehran University. A total of eighty students were divided into two groups of forty. In the first group the periapical technique was taught without laser guided indicator, while in the second group laser guided indicator was applied in training the students. All students took X-rays from the phantoms. Laser guided indicator is made of one low power red laser diodes.Totally 560 X-rays were taken and the technical errors and the quality of X-rays were evaluated. Data were analyzed statistically using Mann-Whitney and Chi Square tests (&alpha=0.05). Results: The X-rays taken by students showed significant differences in cone cutting (P<0.001), and overlapping (P<0.001) between the two study groups. In the subjective review of X-ray quality, the difference was also significant (P=0.03). Conclusion: The use of laser guided indicator as a training aid seems to be practical for easier learning of central ray adjustment and reduction of technical errors in taking X-rays by dental students.